Cardiac splicing as a diagnostic and therapeutic target - Gotthardt, Michael; Badillo-Lisakowski, Victor; Parikh, Victoria Nicole; Ashley, Euan; Furtado, Marta; Carmo-Fonseca, Maria; Schudy, Sarah; Meder, Benjamin; Grosch, Markus; Steinmetz, Lars; Crocini, Claudia; Leinwand, Leslie (Nature reviews. Cardiology, 2023)
Despite advances in therapeutics for heart failure and arrhythmias, a substantial proportion of patients with cardiomyopathy do not respond to interventions, indicating a need to identify novel modifiable myocardial pathobiology. Human genetic variation associated with severe forms of cardiomyopathy and arrhythmias has highlighted the crucial role of alternative splicing in myocardial health and disease, given that it determines which mature RNA transcripts drive the mechanical, structural, signalling and metabolic properties of the heart. In this Review, we discuss how the analysis of cardiac isoform expression has been facilitated by technical advances in multiomics and long-read and single-cell sequencing technologies. The resulting insights into the regulation of alternative splicing — including the identification of cardiac splice regulators as therapeutic targets and the development of a translational pipeline to evaluate splice modulators in human engineered heart tissue, animal models and clinical trials — provide a basis for improved diagnosis and therapy. Finally, we consider how the medical and scientific communities can benefit from facilitated acquisition and interpretation of splicing data towards improved clinical decision-making and patient care.